Integrative bioethics as an original SE-European "product" - Čović, Ante (Array, 2011)
Presented will briefly be the idea of integrative bioethics, conceived within the region of SE Europe and developed into a rounded-off concept within a broader international bioethics project. Integrative bioethics will be presented in three aspects: 1) as a programme ; 2) as a project, and 3) as a concept. Since the beginning, integrative bioethics has been oriented toward the programme task of "bioethics Europeanisation", clearly charted already at the international conference "Bioethics in South- and SE Europe: chances for an integrative-ethical refl exion in front of the European intercultural differences background" (Inter-University Centre, Dubrovnik, October 1-3, 2004). With that conference, also a great bioethics project was launched developing and institutionalizing bioethical collaboration in SE-European region, in which the bioethicists from almost all SE-European countries were participating, as well as from Italy, Austria, and Germany. Within the project, several institutions have been developed (Bioethical Forum for SE Europe, Integrative Bioethics Summer School, Referral Centre for Bioethics in SE Europe). The most important achievement of the project certainly has been the innovative concept of integrative bioethics, which has become the ideological basis of the entire project and a recognizable contribution to the development of bioethics in global relations. In its substantial dimension, integrative bioethics is characterized by a broad field spanning from moral dilemmas in medical practice and biomedical research, determination of the moral status of nonhuman living beings, thematizing of ecological issues, of the role of science and technology in modern civilization, debate on the character of our epoch and the signs of the exchange of epochs, all up to the theoretical foundation of a new universal-historical epoch. In it methodological aspect, integrative bioethics is characterized by an expressed interdisciplinarity, respect for and including into the debate of a relevant circle of special scientific disciplines, but also a circle of non-scientific perspectives encompassed by the concept of "cultural perspectives". Within that context, the notion of pluri-perspectivism has emerged as a methodological determination of integrative bioethics, incorporating scientific and cultural perspectives.